Why Satisfied Consumers do not Repurchase ? The Perspective of Attribution Theory on Repurchase Intention - Yoo, Kun Woo; Kim, Sung Eun (Indian Journal of Marketing, 2020)
Satisfied consumers may switch to another brand instead of repurchase. This study focused on whether the cause of satisfaction is attributed internally or externally and how these attributions can influence the repurchase intention differently among Korean consumers. The data set of 198 respondents were collected on internal and external attribution, knowledge, switching cost, and repurchase intention. The findings indicated that internal attribution did not mediate between consumer satisfaction and repurchase intention ; whereas, external attribution mediated between consumer satisfaction and repurchase intention. Second, consumers with high knowledge had a positive influence on repurchase intention through external attribution rather than internal attribution. Lastly, satisfied consumers had a positive effect on repurchase intention for those who attributed internally only if they perceived the switching cost. The study provided strategies for satisfied consumers with their purchased products who may not necessary repurchase. Furthermore, marketers should consider developing new products with unique and new properties or functions by managing the knowledge level of consumers. This research indicated for the first time that external attribution mediates between satisfaction and repurchase intention ; whereas, internal attribution does not mediate between satisfaction and repurchase intention.